A critical assessment of microbial-based antimicrobial sanitizing of inanimate surfaces in healthcare settings - Fijan, Sabina; Kürti, Peter; Rozman, Urška; Šostar Turk, Sonja (Frontiers in Microbiology, 2024)
The global rise in antimicrobial resistance (AMR) poses a significant public health threat, especially in healthcare settings where controlling the spread of antimicrobial genes is crucial. While person-to-person transmission remains the primary route for healthcare-associated infections (HAIs), hospital surfaces serve as key reservoirs for antimicrobial-resistant microorganisms. Regular cleaning and disinfection of these surfaces are essential. Microbial-based products for sanitizing hospital surfaces have emerged as promising tools to combat HAIs and AMR. However, a review of 32 publications found inconsistencies and potential risks. 15 publications included hospital-based trials, whilst the rest were either in vitro or in situ assays, reviews, book chapters or commentaries. In most of the hospital-based studies, specific strains of applied microorganisms were not identified, and the term "probiotic" was inaccurately used. These products mainly featured spores from Bacillus and Priestia genera, mainly hypothesized to work through competitive exclusion. Most hospital-based studies have shown that the application of microbial-based products resulted in a significant reduction of pathogens on surfaces, thereby contributing to a decrease in the incidence of healthcare-associated infections (HAIs). Further research is however needed to understand the effectiveness, mechanisms of action and safety of microbial-based sanitizing agents. Strain-level identification is crucial for safety assessments, yet many reviewed products lacked this information. Consequently, there's a need for rigorous safety evaluations within existing regulatory frameworks to ensure the efficacy and safety of microbial-based cleaning products in healthcare settings.